C-reactive Protein to Albumin Ratio as a Predictor of Infectious Etiology in Patients Admitted to General Medicine: A Single-center Prospective Observational Study - Arup Kumar Sarma; Ashabari Das; Bandana Thakuria; Priyam Saikia (Archives of Medicine and Health Sciences)
Background and Aim: Procalcitonin (PCT) is widely used to predict progression to sepsis, but PCT is expensive, time-consuming, and may not be routinely available, whereas parameters such as total leucocyte count (TLC), neutrophil and lymphocyte percentage, C-reactive protein (CRP), and albumin are routinely done as initial workup of patient. Recently, CRP to albumin ratio (CAR) has received a great deal of attention as a marker of inflammation. Hence, we aimed to evaluate CAR ratio as a predictor of likelihood of progression to sepsis and to compare the ability of CAR and neutrophil to lymphocyte ratio (NLR) for the prediction of likelihood to progression of sepsis. Materials and Methods: We selected 64 patients above 12 years of age with clinical suspicion of sepsis and in whom PCT level was available in first 48 h. TC, neutrophil, lymphocyte, CRP, and albumin were also obtained as part of routine investigation and NLR and CAR were calculated. We evaluated the diagnostic performance of each of these parameters through area under the receiver operating characteristics curve. Results: It was seen that in patients of CAR > 40, an infectious cause was very likely. High levels of CAR could predict progression to sepsis (P < 0.001) and CRP alone also showed similar results (P < 0.0131). In contrast, TLC, neutrophil, lymphocyte, NLR, and albumin alone were found to be poor predictors of infective etiology and likelihood of progression to sepsis. Conclusion: CAR ratio is a good predictor of likelihood of progression to sepsis in patients presenting with clinical features of possible infection and its predictive power is better that NLR.